Incarceration and the restriction in the enjoyment of the rights of prisoners - Danjuma, Ibrahim; Rohaida Nordin,; Sale, Muhammad Musa (Penerbit Universiti Kebangsaan Malaysia, 2018)
Human rights are universal standards that protect and safeguard all persons from severe mistreatments and abuses. The notion of human rights is grounded on the recognition that “all human beings are born free and equal in dignity and rights” and everyone is therefore “entitled to all rights and freedoms” contained in the human rights law. All the rights and freedoms guaranteed by the law can however, be subjected to a restriction according to other laws of the land. The respect and protection for the human rights of a person depend upon his status, whether he is an adult or a child; a prisoner or freeman; male or female. It was argued that prisoners are entitled to all their personal rights as well as personal dignity that are not temporarily taken away by the law or necessarily inconsistent with the circumstances in which they have been placed. The question to ask is do the laws expressly stated the rights that are not forfeited as a result of incarceration? If the answer is in the negative, what is the litmus test to employ in order to determine the rights that are not lost as a result of incarceration? This study examines relevant laws, published and unpublished reports in order to answer the above posed questions.